Configurations of barriers to digital transformation in Portuguese SMEs and the effects of DT to the employees - Barata, Miguel João Jerónimo (2024)
Digital transformation (DT) is sweeping all businesses, and fundamentally changing processes, relevant skills, frontiers, and outlook for HRM. Although universally recognised as an unavoidable and beneficial factor for business, DT requires resources and positive attitudes conducive to its implementation. However, it may also be associated with perceived threats, such as impacts as regards both HR quantitative and qualitative dimensions, that hamper the willingness to implement it. This may be especially felt in SMEs due to lower resource availability. Likewise, DT barriers tend to be treated as a cumulative set of factors that contribute each one to a certain level of resistance to DT implementation. Still, it is most likely that not only are these DT barriers working together as clusters (they tend to co-occur) as they may operate as bundles, i.e. they may determine the resistance as configurations of DT barriers and not as simple cumulative effects. This study was designed to test to which extend DT barriers are present in Portuguese SMEs, how much they are associated among each other, and what configurations are associated to the expected impact on both HR quantitative and qualitative. With a sample of 30 SMEs managers a hierarchical cluster analysis showed groups of DT barriers, which were integrated in a fsQCA analysis, to reveal four configurations of DT barriers that account for qualitative HR impacts. As per the quantitative impacts, the analysis did not yield any configuration as the vast majority stated no changes are expectable at this level.